Duration of Atrial Fibrillation Episodes and Implications for the Thromboembolic Risk - Neves, David (2015)
Introduction: Atrial fibrillation is the most common chronic arrhythmia in clinical practice, which is associated with a well known increased thromboembolic risk. The use of oral anticoagulants in this context is well established. However, there are some gaps in information that warrant further studies, such as the duration of an atrial fibrillation event that is long enough to increase the risk of embolic phenomena. This may be of important clinical concern, particularly in patients with cardiac implanted devices, in which very short periods of asymptomatic atrial fibrillation are often detected.Material and Methods: We performed a critical review on the association of brief atrial fibrillation episodes and thromboembolic events, based on available literature indexed on PubMed.Results: After initial selection of abstracts and checking of references a final pool of 8 papers were analysed; seven describing studies with cardiac implanted devices and one with Holter monitoring. Four of the studies addressed this issue with a ‘daily burden’ approach rather than single episode duration. The risk increases with the magnitude of atrial fibrillation burden, with 5 minutes of atrial fibrillation in one day being the shortest time shown to independently predict thromboembolic events.Discussion: The formation of an intracardiac thrombus, and respective embolic potential, is a dynamic process resulting from the interaction of anatomical and functional variables. The individual risk will depend on these factors. The association between embolic events and short atrial fibrillation episodes is evident, although the mechanism is not obvious, given the time discrepancy that is frequently observed between atrial fibrillation episode and clinical event.Conclusions: An atrial fibrillation burden of 5 minutes in one day has been shown to be independently associated with a significantly increased risk, although the cause-effect mechanism is not clear. A standardized way to select patients with short-duration atrial fibrillation periods that will have a meaningful benefit of chronic oral anticoagulation is still to define. Therefore, decisions should be made in an individualized manner.